Еffect of the process of flaking of einkorn (Тriticum monococcum L.) on some basic chemical properties and biologically active compounds in the flaked product - Ivan Dimov; Gjore Nakov; Nastia Ivanova; Viktorija Stamatovska (Journal of Central European Agriculture, 2019)
Nowadays, flaked product became quite popular. The aim of the present paper is to study the effect of the process of flaking of einkorn (Triticum monococcum L.) on some basic chemical properties, the biologically active substances and the antioxidant activity of the flaked product. The chemical parameters (contents of moisture, ash and fats) were determined according to ISO standard methods. Protein content was determined by the method of Lowry. The following biologically active compounds were also determined: total polyphenols, antioxidant activity (% DPPH) and total carotenoids. The analyses carried out showed that the flaking has certain effect, although to small extent, on the values of the properties of the flaked einkorn studied. The moisture content and the total amount of carotenoids were found to decrease while the amounts of fats, proteins and total polyphenols increased. The results obtained from the analyses of the flaked product were compared to these of wholegrain einkorn flour and it was found that the differences were considered to be immaterial although some of them were statistically significant. It was found also that the process of flaking does not affect the amount of mineral substances and the antioxidant activity of the flaked einkorn compared to einkorn flour.